A California Multidisciplinary Juvenile Court: Serving Sexually Exploited and At‐Risk Youth. (January 2016) - Liles, Brandi D.; Blacker, Dawn M.; Landini, Jenny L.; Urquiza, Anthony J.
Abstract : Research suggests that 90% of youth in the juvenile justice system have experienced at least one traumatic event (Arroyo, 2001 ). One such traumatic event is the commercialized sexual exploitation of children and youth (CSEC). Over the past decade, governmental organizations and community agencies have recognized that the sexual exploitation of children is a significant problem in the United States. In California alone, human trafficking task forces have identified 1200 youth as victims of sexual exploitation from 2010 to 2012 (Walker, 2013 ). Youth who have experienced sexual exploitation often become involved in the juvenile justice system and present with unique challenges and needs. This article reviews recent public policy and community responses related to the needs of CSEC youth involved in the juvenile justice system. A case example from Sacramento, CA, is used to illustrate the key components, innovations, multidisciplinary collaborations, and challenges of creating a specialized court. Copyright © 2016 John Wiley & Sons, Ltd.